2015
DOI: 10.1111/and.12510
|View full text |Cite
|
Sign up to set email alerts
|

Impact of testicular histopathology as a predictor of sperm retrieval and pregnancy outcome in patients with nonobstructive azoospermia: correlation with clinical and hormonal factors

Abstract: In this study, our objective was to evaluate the impact of testicular histopathology on the outcome of intracytoplasmic sperm injection (ICSI) cycles of patients with nonobstructive azoospermia and correlate with clinical and hormonal parameters. For this purpose, 271 patients with nonobstructive azospermia (NOA) who underwent testicular sperm extraction (TESE) for ICSI cycles were retrospectively evaluated for sperm retrieval, fertilisation, embryo cleavage, clinical pregnancy and live birth rates among diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 35 publications
3
33
0
Order By: Relevance
“…Overall, the rate of successful sperm retrieval in NOA patients was previously estimated as 53% [28]. Rates varied for different histological subtypes of NOA: 81% for HS, 21% for MA, and 31% for SCO subtypes [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the rate of successful sperm retrieval in NOA patients was previously estimated as 53% [28]. Rates varied for different histological subtypes of NOA: 81% for HS, 21% for MA, and 31% for SCO subtypes [28].…”
Section: Resultsmentioning
confidence: 99%
“…Rates varied for different histological subtypes of NOA: 81% for HS, 21% for MA, and 31% for SCO subtypes [28]. In our cohort of NOA samples with known histological subtypes and measured TEX101 (20 out of 26 samples in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Spermatogenic function of the testis needs to be suitable in various sex hormone parameters. Recent reports of the predictive factor of sperm retrieval investigated FSH, LH, inhibin‐B, and T . In many cases of high FSH levels, there is a high possibility that sperm retrieval will fail.…”
Section: Discussionmentioning
confidence: 99%
“…One effective technique for sperm retrieval that has been reported in a number of different studies is microdissection TESE (MD‐TESE), which is performed for NOA, and simple TESE that is performed for OA . According to recent reports, blood hormone levels, follicle‐stimulating hormone (FSH), luteinizing hormone (LH), inhibin‐B, testosterone (T), testicular volume, Y chromosome microdeletion, and chromosome inspection are used as predictors in sperm retrieval . After retrieval, one study reported a comparison between fresh and vitrified oocytes that were used in ICSI with fresh testicular sperm.…”
Section: Introductionmentioning
confidence: 99%
“…A study found that sperm retrieval rates were positively related to increased testicular volume and decreased follicle stimulating hormone (FSH) levels in men with NOA (Ghalayini et al, ). In addition, one study found that testicular histology influenced sperm retrieval and fertilisation rates but not pregnancy or live birth rates for men with NOA undergoing ICSI (Guler et al, ).…”
Section: Introductionmentioning
confidence: 99%